Analysis of Students Response to Implementation Merdeka Belajar Based Information Technology After Pandemic - Amina Divina; Shirly Rizki Kusumaningrum; Radeni Sukma Indra Dewi (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2022)
Technology-based learning has been very popularly used since the Covid-19 pandemic until now. Information technology provides various learning resources to make it easier for students to study independently, anytime, and anywhere in accordance with the Merdeka Belajar curriculum program. The purpose of this study was to see students’ response to the Merdeka Belajar curriculum-based information technology. The research method used is descriptive quantitative method and data collection through questionnaires given to 78 fourth grade students in Sampang District. The software used by students shows 100% using social media in the form of WhatsApp and 73.07% using Google Meet to communicate with teachers. Then as many as 100% used Google, 35.89% used Ruang Guru, 67.94% used Brainly, 53.84% used Wikipedia, and 60.25% used YouTube to find information. 33.3% used Quizizz and 46.15% used the Duolingo application to get practice questions. While students who find it easy to understand the material through digital media as many as 94, 87% and 5.12% find it difficult. Although some students have difficulty, all students or 100% of students feel happy to use digital media as a tool to support the learning process.